Lakbay reinforcing creative teaching strategies in junior high school history classes with gamified learning resources - Dela Cruz, Kyla Lynnea Y.
Araling Panlipunan is a core subject in Secondary Education that aims to prepare students to be responsible, informed citizens who will play active roles in society in the future. However, teachers face challenges with their students' lack of interest in the subject, particularly history, due to its perceived irrelevance to their lives at present. This compels teachers to adapt their methods to align with students' interests, which are influenced by rapidly changing trends and the digital age. Gamified learning has been a successful strategy that teachers have been using to increase classroom engagement. Among the tools that they use for gamified activities are Kahoot and Slido, though these primarily support content-based learning. Recognizing the importance of teaching students values through history, there arises a need for supplementary tools and strategies that will not only increase student engagement but also improve learning outcomes by balancing content and competence-based learning. As a result, this study suggests a gamified classroom resource that encourages students to develop a deeper understanding of History through exploring how societal conditions would have been impacted if events had unfolded differently at that time. Usability testing with teachers and administrators from select public and private schools in Novaliches, Quezon City, yielded positive results. The intervention has been regarded as an innovative tool with a positive overall impact on pedagogy, introducing a learning approach that is aligned with the preferred teaching methods in the forthcoming Matatag curriculum.